Republic of Lithuania : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 1999)
This 1999 Article IV Consultation highlights that Lithuania has made impressive progress in macroeconomic stabilization and market transition. Following the introduction of the currency board in 1994, inflation has come down rapidly, and market reforms have provided a sound basis for economic recovery. The economy cooled down rapidly starting in the third quarter of 1998, while inflation continued on a downward trend. The current account deficit widened in the second half of 1998 but subsequently contracted. Real GDP growth came to a halt in the fourth quarter of 1998.